Pseudo-Slant Submanifolds of a Locally Decomposable Riemannian Manifold - Atceken, Mehmet; Dirik, SÄuleyman; Yildirim, ÄUmit (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
In this paper, we study pseudo-slant submanifolds of a locally decom- posable Riemannian manifold. We give necessary and suffcient conditions for distributions which are involued in the definition of pseudo-slant sub- manifold to be integrable. We search these type submanifolds with parallel canonical structures and we obtain some new results.